2014
DOI: 10.1177/0886260513520231
|View full text |Cite
|
Sign up to set email alerts
|

Media Portrayals of Female Perpetrators of Intimate Partner Violence

Abstract: Preventing intimate partner violence (IPV) is a public health priority. An important component of designing prevention programs is developing an understanding of how media portrayals of health issues influence public opinion and policy. To better understand the ways in which media images may be informing our understanding of IPV, this study content analyzed portrayals of IPV in news media articles. Stratified media outlets were used to obtain a representative sample of daily newspapers based on their designate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 37 publications
1
34
1
4
Order By: Relevance
“…Even in the weak violence condition, participants still rated IPV as serious. Content analyses of news stories have shown that IPV with low levels of violence is not frequently depicted in new stories (e.g., Carlyle, Scarduzio, et al, 2014;Sellers et al, 2014). However, the current study finds that presentations of low-severity violence may still impact the individuals reading news stories.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Even in the weak violence condition, participants still rated IPV as serious. Content analyses of news stories have shown that IPV with low levels of violence is not frequently depicted in new stories (e.g., Carlyle, Scarduzio, et al, 2014;Sellers et al, 2014). However, the current study finds that presentations of low-severity violence may still impact the individuals reading news stories.…”
Section: Discussioncontrasting
confidence: 68%
“…Perceptions of IPV also differ when male and female perpetrators use severe violence. For example, female perpetrators who use severe violence, such as killing their partner, are perceived as abnormal or socially deviant (Carlyle, Scarduzio, et al, 2014). Further, male perpetrators who use severe violence are depicted more frequently in news stories because they are more likely to use severe violence than female perpetrators, and thus their behavior is normalized (see Carlyle et al, 2008).…”
Section: Severity Of Violencementioning
confidence: 99%
See 2 more Smart Citations
“…3) Studies that show similarity in female and male perpetration, revealing gender symmetry in domestic violence (Carlyle, Scarduzio, & Slater, 2014;Chan, 2011;Fincham Cui, Gordon, & Ueno, 2013;Marshall et al, 2011;Sullivan et al, 2010;Walsh et al, 2010;Winstok, 2013;Zanoni et al, 2014).…”
Section: Resultsmentioning
confidence: 99%